The Berlin Brain–Computer Interface: Non-Medical Uses of BCI Technology - Blankertz, Benjamin; Tangermann, Michael; Vidaurre, Carmen; Fazli, Siamac; Sannelli, Claudia; Haufe, Stefan; Maeder, Cecilia; Ramsey, Lenny E.; Sturm, Irene; Curio, Gabriel; Mueller, Klaus R. (Frontiers in Neuroscience, 2010)
Brain-Computer Interfacing (BCI) is a steadily growing area of research. While initially BCI research was focused on applications for paralyzed patients, increasingly more alternative applications in healthy human subjects are proposed and investigated. In particular, monitoring of mental states and decoding of covert user states have seen a strong rise of interest. Here, we present some examples of such novel applications which provide evidence for the promising potential of BCI technology for non-medical uses. Furthermore, we discuss distinct methodological improvements required to bring non-medical applications of BCI technology to a diversity of layperson target groups, e.g., ease of use, minimal training, general usability, short control latencies.